User Interface Analysis Using the Heuristic Evaluation Method in the Astra International Cooperative Application (KAI Apps) - Zaelani, Ahmad; Banowosari , Lintang Yuniar (Information Technology and Science (ITScience), 2025)
This study aims to analyze the usability of the user interface in the Astra International Cooperative (KAI Apps) application using the Heuristic Evaluation method. A quantitative approach was applied through observation of the application and distribution of a Google Form-based questionnaire to 100 respondents selected using the Slovin formula from a population of 100,000 users. The research instrument consisted of 30 statements compiled based on Nielsen's ten Heuristic Evaluation principles, such as visibility of system status, consistency and standards, error prevention, and help and documentation. The data was analyzed using validity and reliability tests, as well as descriptive percentage analysis using SPSS software. The results showed that the Astra Cooperative application scored 86.78%, which is classified as very high, with nine out of ten usability principles rated as good by the majority of respondents. These findings indicate that the application is capable of providing a positive experience for users in accessing cooperative services digitally. However, weaknesses were still found in the aspects of help and documentation, which were considered unclear and not entirely relevant, so that development in the form of tutorials, FAQs, and interactive guides is needed to optimize the user experience.